ANALISIS PENGARUH KREDIT INVESTASI TERHADAP NILAI EKSPOR DI KALIMANTAN BARAT - B01107008, TITIN SURYANI (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled "The Effect of Investment Credit against Export Value in West Borneo". The problem in this study is "What is the investment credit affect exports in West Borneo". While the goal of the study is "to analyze and examine the effect of investment loans to the value of exports in West Borneo". In this study, the authors used descriptive research method to see the effect or the relationship between investment and exports. The model used in this study is a linear regression model. Data obtained sourced from the Central Statistics Agency (BPS) and West Borneo, Indonesia Financial Statistics published by Bank Indonesia province of West Borneo. The test statistic includes the t test and test R2 (coefficient of determination) and Autocorrelation test the classical assumptions. From the research that has been done by the authors concluded that the results of the estimated regression Y = 2003.439 + 5.07E-08X the investment credit has positive and significant impact on the value of exports in West Borneo. Since investment loans have a positive impact on the communities in which the investment was made. Projects are built to create jobs with sufficient income for local people. From the estimation results, it can be explained the effect of the independent variable on the dependent variable is the investment credit has a positive influence on the value of exports, with a 95% confidence level (? = 5%). Based on the results of the test calculations the coefficient of determination (R2) is equal to 0.484747. This means that 48% where the dependent variable explained by the independent variables capable of being used, while 52% where the dependent variable is explained by factors other than study. Based on the test results it can be seen that t (X) was significant at ? = 5% t count greater than t table (10.53630> 1.657870). Thus Ha is accepted, it means the variable investment credit (X) significantly affect Export Value (Y) in West Borneo. Based on Autocorrelation test results, obtained by DW count equal to 2.220241, the conclusions drawn are d_L ? DW <4 - du. This means that the model estimates the autocorrelation test does not happen.